GUGATAN UNI EROPA KE WORLD TRADE ORGANIZATION (WTO) TERHADAP INDONESIA TERKAIT DENGAN KEBIJAKAN LARANGAN EKSPOR BIJIH NIKEL INDONESIA TAHUN 2019 - Hanif, Iga Dhea; Fuadi, Ahmad (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
This study will discuss the lawsuit filed by the European Union to the World Trade Organization (WTO) related to the policy of banning nickel ore exports issued by Indonesia in 2019. The European Union sued Indonesia to the WTO regarding trade barriers because nickel is one of the main raw materials in the manufacture of stainless steel which has long occupied a strategic position in the European Union economy. The reason for the European Union to sue Indonesia even though it does not import nickel ore from Indonesia is the focus of this research.This research is an explanation qualitative research that emphasizes the depth of the data obtained by the researcher. The theory used to analyze the thesis case study is the theory of trade liberalization. The theory of trade liberalization put forward by Adam Smith explains that international trade must be based on the principle of a free market, where the flow of goods from one country to another must be free from all forms of obstacles.This study shows that Indonesia's policy of banning nickel ore exports has made it difficult for the European Union to obtain nickel raw materials for its stainless steel industry. As the world's largest nickel producer, Indonesia's policies have made global nickel supplies scarce and nickel prices higher. This policy also made it difficult for the European Union's stainless steel industry to compete, especially with the Indonesian stainless steel industry, so the European Union chose to sue Indonesia to the WTO.Â Keyword: Export Ban, Nickel, Lawsuit, European Union, Indonesia, WTO